Optimalisasi Pemanfaatan Limbah Rumah Tangga melalui Pendekatan Aquaponik - Onni Meirezaldi; Nila Firdausi Nuzula; Sri Sulasmiyati; Cacik Rut Damayanti; Agung Nugroho Luthfi Imam Fahrudi; Desika Putri Nuraeni; Rayssa Nathasa Arja (ISAS (Indonesian Society of Applied Science), 2025)
Uncontrolled household waste management is an environmental problem that harms public health and ecosystem balance. The circular aquaponics-based organic waste management program in Sambirejo Village aims to reduce environmental pollution and improve community welfare through a sustainable approach. The program is conducted through socialization, technical training, and pilot project construction. The implementation results showed that community awareness of the importance of organic waste management increased significantly. The aquaponic system implemented allows the utilization of organic waste as a source of nutrients for plants and fish in a closed ecosystem, thus reducing dependence on chemical fertilizers and minimizing waste. In addition to providing a positive environmental impact, the program also contributes to improving the community’s economy by harvesting fish and vegetables that can be consumed by themselves or sold. The sustainability evaluation shows that most program participants are committed to developing the system independently, with ongoing technical support and mentoring. This program proves that a community-based approach to organic waste management can be an innovative solution and can be replicated in other areas with similar problems.